2009
DOI: 10.1038/ismej.2009.133
|View full text |Cite
|
Sign up to set email alerts
|

Eukarya 18S rRNA gene diversity in the sea surface microlayer: implications for the structure of the neustonic microbial loop

Abstract: We have previously shown that there is a consistent and reproducible bacterioneuston community in the surface microlayer during a fjord mesocosm experiment. One possible cause of the surface microlayer-specific bacterial community is a surface microlayer-specific protist community selectively grazing on the bacterioneuston. We determined protist community structures using Eukarya 18S rRNA gene denaturing gradient gel electrophoresis (DGGE) and subsequent DGGE band sequencing using DNA samples that were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Replicate samples collected from the surface microlayer (sampling depth $400 mm) and subsurface water (sampling depth 0.75 m) during a phytoplankton bloom experiment in a fjord mesocosm were analyzed using DGGE of Eukarya 18S rRNA gene amplicons. Protist community structure in the surface microlayer samples was different from that in subsurface water, with two taxa appearing to dominate the microlayer samples: Cercozoa and, to a lesser extent, Ciliophora (Cunliffe & Murrell, 2010). This study implies that the protist components of the microbial loop in the fjord surface microlayer are significantly different from those in subsurface water.…”
Section: Food Webs In Surface Microlayersmentioning
confidence: 64%
“…Replicate samples collected from the surface microlayer (sampling depth $400 mm) and subsurface water (sampling depth 0.75 m) during a phytoplankton bloom experiment in a fjord mesocosm were analyzed using DGGE of Eukarya 18S rRNA gene amplicons. Protist community structure in the surface microlayer samples was different from that in subsurface water, with two taxa appearing to dominate the microlayer samples: Cercozoa and, to a lesser extent, Ciliophora (Cunliffe & Murrell, 2010). This study implies that the protist components of the microbial loop in the fjord surface microlayer are significantly different from those in subsurface water.…”
Section: Food Webs In Surface Microlayersmentioning
confidence: 64%
“…, Montes‐Hugo and Alvarez‐Borrego ). Only one previous mesocosm‐based study has used molecular techniques (DGGE analysis of 18S rRNA genes) to characterize neustonic protist diversity (Cunliffe and Murrell ). The study sequenced 19 excised DGGE bands, only two of which were important in the neuston assemblage.…”
Section: Environmental Parameters Water Column Phytoplankton Cell Comentioning
confidence: 99%
“…Studies aiming to determine the diversity of protists in the neuston have almost exclusively relied upon microscope-based observations, pigment analysis and flow cytometry (Hardy and Valett 1981, De Souza Limaa and Chretiennot-Dinet 1984, Hardy and Apts 1984, 1989, Joux et al 2006, Montes-Hugo and Alvarez-Borrego 2007. Only one previous mesocosm-based study has used molecular techniques (DGGE analysis of 18S rRNA genes) to characterize neustonic protist diversity (Cunliffe and Murrell 2010). The study sequenced 19 excised DGGE bands, only two of which were important in the neuston assemblage.…”
mentioning
confidence: 99%
“…Aller et al (2005) found that the EF for bacteria and virus abundances were 10 and 7, respectively. Protistan community composition in the SML is different from the underlying waters and is enriched in some taxa (Joux et al, 2006;Cunliffe and Murrell, 2010;Taylor and Cunliffe, 2014). Joux et al (2006) proposed that buoyant particles and bubbles play a role in the enrichment of the SML with specific taxa.…”
Section: Introductionmentioning
confidence: 99%